Badania Pewnych Reologicznych Własności Elastooptycznych Kilku Żywic Poliestrowych (II) - Pindera, J.T. (Engineering Transactions, 1959)
This second part of the paper on the rheologic photoelastic properties of certain polyester resins embodies a discussion of test results, their interpretation, and comparison with results obtained by other authors. Static tests of creep and recovery were conducted with test-pieces in the form of a thin wedge, stretched with a constant force. The real values of stresses are given. The rheologic photoelastic properties of the CR-39, VP-1527 and P-6 resins were tested for tension with a constant force in a broad range of test durations. The investigations of creep and recovery for bending were performed with test-pieces acted on by a concentrated force constant or periodic. Comparing the results obtained with those of other investigations, it is shown how fundamental is the influence of measurement technique on test results. The method of investigation used is subjected to a detailed analysis. In particular, the influence of the manner of applying the load, and the influence of the stress field are discussed, together with the alternating character of the load. The rheologic diagrams obtained are interpreted from the point of view of the structure of the material and the rheologic model used. It is shown that the character of creep and recovery of the resins in question may be explained by assuming that the photoelastic effect observed is consequent on the history of the orientation of each anisotropic group. On the basis of the Kelvin-Maxwell model, it is shown that a linear rheologic model of this type does not describe the creep and the recovery of the resins tested. For the CR-39 resin, the conditions are established as being satisfied by the rheologic formulae, the non-linear character of the phenomenon being shown. It is demonstrated that the structure of rheologic materials and the rheologic relations should, for the resins tested, be based on accurate investigations of physical properties and structure. It is found that the influence of alternating loads on the rate of the recovery is fundamental. It is shown also that for the resins tested there exists a relation between the phenomenon of stress freezing and that of optical creep.